Monte Carlo Event Generator updates, for tau pair events at Belle II energies - Sw. Banerjee, D. Biswas, T. Przedzinski, Z. Was (SciPost Physics Proceedings, 2025)
The Monte Carlo for lepton pair production and $τ$ decays consist of KKMC for lepton pair production, tauola for $τ$ lepton decays and photos for radiative corrections in decays. An effort for adaptation of the system for precision data to be collected at Belle II experiment lead to extension of phase space generation modules both in photos and tauola to enable decays and/or radiative corrections of additional light lepton pairs. The phase-space and matrix element parts of the programs are separated, that is why extension to processes where lepton pair is produced through narrow resonances, like dark photon, was straight forward. In the present version of tauola, the list of $τ$ decay channels is enriched with multitude of exotic ones, useful for searches of new physics. The hadronic currents parametrization of main decay channels is prepared for basic simulation in the experiment. The basis for future work on precise fits of hadronic currents including Machine Learning is retained, but development of necessary software solutions is left for the forthcoming years. Presented programs versions are available in stand-alone format from GitLab or through the basf2 system of Belle II software. Official distribution web pages, documenting programs tests, are retained but not necessarily up to date.